2015
DOI: 10.1002/nbm.3335
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring dynamic alterations in calcium homeostasis by T1‐mapping manganese‐enhanced MRI (MEMRI) in the early stage of small intestinal ischemia–reperfusion injury

Abstract: Manganese-enhanced MRI studies have proven to be useful in monitoring physiological activities associated with calcium ions (Ca(2+)) due to the paramagnetic property of the manganese ion (Mn(2+)), which makes it an excellent probe of Ca(2+) . In this study, we developed a method in which a Mn(2+)-enhanced T1 -map MRI could enable the monitoring of Ca(2+) influx during the early stages of intestinal ischemia-reperfusion (I/R) injury. The Mn(2+) infusion protocol was optimized by obtaining dose-dependent and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Mn 2+ is a divalent cation similar in ionic radius and chemical properties to Ca 2+ that can pass through various Ca 2+ channels, and its paramagnetic properties make it a potent MRI spin lattice relaxation time constant (T1) contrast agent (Naruse & Sokabe, 1993;Dryselius et al 1999;Takeda, 2003;Waghorn et al 2009). Manganese-enhanced MRI (MEMRI) has been used to assess various conditions associated with Ca 2+ ions, such as brain activity (Cha et al 2016;Schroeder et al 2016), neuronal tract tracing and axonal transport (Inoue et al 2011;Majid et al 2014), injury (Rodriguez et al 2016;Yang et al 2016), ischaemia-reperfusion (Zhao et al 2015) and cardiac function (Chen et al 2012;Andrews et al 2015). However, it has never been used to assess aberrant Ca 2+ handling in dystrophic skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 2+ is a divalent cation similar in ionic radius and chemical properties to Ca 2+ that can pass through various Ca 2+ channels, and its paramagnetic properties make it a potent MRI spin lattice relaxation time constant (T1) contrast agent (Naruse & Sokabe, 1993;Dryselius et al 1999;Takeda, 2003;Waghorn et al 2009). Manganese-enhanced MRI (MEMRI) has been used to assess various conditions associated with Ca 2+ ions, such as brain activity (Cha et al 2016;Schroeder et al 2016), neuronal tract tracing and axonal transport (Inoue et al 2011;Majid et al 2014), injury (Rodriguez et al 2016;Yang et al 2016), ischaemia-reperfusion (Zhao et al 2015) and cardiac function (Chen et al 2012;Andrews et al 2015). However, it has never been used to assess aberrant Ca 2+ handling in dystrophic skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is possible that the assessment of alterations in the diffusion of other ions is more sensitive to detect intestinal perfusion changes. For instance, it has been shown that changes in calcium (Ca 2+ ) homeostasis due to early I/R injury can be detected using manganese-enhanced magnetic resonance imaging (MRI) in a rat model [ 31 ]. The investigation of Ca 2+ however is not feasible using a low-field scanner such as the NMR-MOUSE.…”
Section: Discussionmentioning
confidence: 99%
“…Also, while conventional computed tomography (CT) and magnetic resonance imaging (MRI) are used to diagnose intestinal ischemia injury, they cannot evaluate changes in hemoglobin concentration and blood oxygen saturation in tissue. Therefore, it is necessary to establish a morphological diagnosis by CT and MRI and further evaluate the status of intestinal blood flow (7,8) by other means. Several commonly used detection techniques, such as sidestream dark-field imaging (9), spectrophotometry, and laser Doppler blood flow measurement, have been used to study intestinal microcirculation (10).…”
Section: Introductionmentioning
confidence: 99%